Appendicitis Secondary to Trauma following a Camel Kick: Case Report and Review of Literature. (7th January 2021) - Toffaha, Ali; Al-Yahri, Omer; Hijawi, Zainab; Al-Mudares, Saif; Al-Tarakji, Mohannad; Shahid, Fakhar; Ali, Syed Muhammad
Abstract : Introduction . Independently, trauma and appendicitis are two of the most common conditions in surgical practice. Rarely, both conditions may coexist, which raises the controversy whether it is merely a coincidence or trauma may lead to acute appendicitis. Presentation of Case . We report a case of acute appendicitis after blunt abdominal trauma caused by a camel hoof kick to the abdomen in a young man and discuss the potential underlying pathophysiologic mechanisms with review of the pertinent literature. Conclusions . Blunt abdominal trauma caused by a camel kick to the abdomen requires a close observation of the patients. A camel kick may increase intra-abdominal pressure and cause internal organ injury including the appendix. Therefore, acute appendicitis should be considered in differential diagnosis in any patient with abdominal pain resembling appendicitis following blunt abdominal trauma.